Sustainable tourism after COVID-19 insights and recommendations for Asia and the Pacific - Asian Development Bank (Manila, Philippines Asian Development Bank, 2021)
Examines tourism in Asia and the Pacific, the impacts on it of the coronavirus disease (COVID-19) pandemic, and how it might be reset to contribute more effectively to the Sustainable Development Goals.
Executive Summary - - Introduction - - Pre-COVID-19: Tourism and Sustainable Development in Asia and the Pacific - - COVID-19 Impacts and Responses in Asia and the Pacific - - Expert Insights - - Future Pathways and Opportunities - - Recommendations for Decision-Makers - - Appendix.
Keywords: Sustainable development -- Asia and the Pacific